Post-transcriptional regulation dominates protein biosynthesis in Landoltia punctata under biogas slurry stress - Gong, Xin-Li; Li, Jun-Yi; Li, Jia-Zhou; Ran, Cheng; Zhou, Le-Le; Zhou, Tian; Su, Huan-Huan; Lu, Ting-Ting; Zhang, Shi-Lin (Frontiers in Plant Science, 2025)
IntroductionDuckweed represents a promising alternative protein source, yet enhancing its protein content remains essential for large-scale applications. This study investigated how high nitrogen and phosphorus stress from biogas slurry affects protein accumulation in Landoltia punctata and explored the underlying molecular regulatory mechanisms.MethodsL. punctata were cultivated in 1/5 strength Hoagland medium supplemented with 0-5% pig farm biogas slurry. The experimental groups showing the highest (4%) and lowest (0%) protein content were selected for integrated transcriptomic and proteomic analyses. Differentially expressed genes (DEGs) and proteins (DEPs) were identified and functionally characterized.ResultsBiogas slurry treatments significantly increased crude protein content in a concentration-dependent manner, with the 4% treatment showing the highest value of 24.18% compared to 18.13% in controls. Multi-omics analysis revealed a low correlation between mRNA and protein expression (R=0.1387), indicating dominant post-transcriptional regulation. Ribosomal proteins were significantly upregulated at the protein level without corresponding transcriptional changes, suggesting enhanced translation efficiency. Concurrently, key enzymes in amino acid catabolism were downregulated, potentially conserving substrates for protein synthesis. The photosynthetic system showed coordinated downregulation at both transcriptional and protein levels, with suppression of light-responsive genes and carbon fixation pathway components, indicating redirected carbon and energy flows toward nitrogen assimilation.DiscussionBiogas slurry enhances duckweed protein accumulation primarily through post-transcriptional regulation. Enhanced translation efficiency coupled with metabolic reallocation from photosynthesis to nitrogen assimilation optimizes protein synthesis. This first multi-omics perspective on post-transcriptional regulation under biogas slurry stress provides theoretical support for molecular breeding of high-protein duckweed.